2021
DOI: 10.1158/1078-0432.ccr-20-3017
|View full text |Cite
|
Sign up to set email alerts
|

Combining Neratinib with CDK4/6, mTOR, and MEK Inhibitors in Models of HER2-positive Cancer

Abstract: Purpose: Neratinib is an irreversible, pan-HER tyrosine kinase inhibitor that is FDA approved for HER2-overexpressing/amplified (HER2 þ ) breast cancer. In this preclinical study, we explored the efficacy of neratinib in combination with inhibitors of downstream signaling in HER2 þ cancers in vitro and in vivo.Experimental Design: Cell viability, colony formation assays, and Western blotting were used to determine the effect of neratinib in vitro. In vivo efficacy was assessed with patient-derived xenografts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 67 publications
2
32
0
Order By: Relevance
“…To the best of our knowledge, this present preclinical study is the first to show that neratinib can potentially induce TGI in both HER2+ breast cancer and TNBC when cotreated with inhibitors of the PI3K/Akt-mTOR or MAPK pathway. Our findings in HER2+ breast cancer were supported by a recent study by Zhao et al [27]. We also reported the novel finding of the potential anti-tumor effect of neratinib in both in vitro and in vivo xenograft models.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, this present preclinical study is the first to show that neratinib can potentially induce TGI in both HER2+ breast cancer and TNBC when cotreated with inhibitors of the PI3K/Akt-mTOR or MAPK pathway. Our findings in HER2+ breast cancer were supported by a recent study by Zhao et al [27]. We also reported the novel finding of the potential anti-tumor effect of neratinib in both in vitro and in vivo xenograft models.…”
Section: Discussionsupporting
confidence: 89%
“…Intriguingly, the studies by others also demonstrated a significant antitumor effect when the PI3K inhibitor was combined with anti-HER2 therapy. Neratinib has a synergistic antitumor effect with everolimus in PIK3CA-mutated HER2+ breast cancer patient-derived xenograft models and with trametinib in HER2-mutated HER2+ breast cancer patient-derived xenograft models [27]. Combination treatment with lapatinib and ipatasertib overcomes resistance to anti-HER2 therapy in PIK3CA-mutant HER2+ breast cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies searching for effective combination therapies that enhance CDK4/6i efficacy in ER-positive breast cancer have focused on concomitant inhibition of growth factor signaling pathways. Combined inhibition of CDK4/6 and growth factor receptors, such as HER2 and FGFR, or the downstream pathway members, such as PI3K, PDK1, and mTOR, has demonstrated synergy or at least heightened effects [36,[65][66][67][68][69]. In some cases, the effect of combined inhibition of CDK4/6 and a growth factor pathway is enhanced cytostasis or senescence [36,65,69], and in others, the effect is apoptosis [30,[66][67][68].…”
Section: Interaction With Oncogenic Kinase Signaling Circuitsmentioning
confidence: 99%
“…Combined inhibition of CDK4/6 and growth factor receptors, such as HER2 and FGFR, or the downstream pathway members, such as PI3K, PDK1, and mTOR, has demonstrated synergy or at least heightened effects [36,[65][66][67][68][69]. In some cases, the effect of combined inhibition of CDK4/6 and a growth factor pathway is enhanced cytostasis or senescence [36,65,69], and in others, the effect is apoptosis [30,[66][67][68]. The combination of ET, CDK4/6, and PI3K inhibition results in maximal growth inhibition in ER-positive breast cancer models [30].…”
Section: Interaction With Oncogenic Kinase Signaling Circuitsmentioning
confidence: 99%
See 1 more Smart Citation